2018
DOI: 10.1007/s10384-018-0574-9
|View full text |Cite
|
Sign up to set email alerts
|

Spectral domain optical coherence tomography and fundus autofluorescence findings in cytomegalovirus retinitis in HIV-infected patients

Abstract: Although the number of examined eyes was limited, SD-OCT and FAF provide new information in various stages of CMV retinitis in patients with HIV infection that is not obtainable by conventional examination and which may be of great benefit when screening for the initial stage of CMV retinitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 33 publications
1
12
0
Order By: Relevance
“…OCT characteristics of patients in the CMVR group: In the present study, the thickness of various macular regions in the CMVR group generally increased, and the reflection of the entorretina increased. [10] This is consistent with the study results reported by Japanese scholar Yashiro et al, [11] but is contradictory to the study results reported by Pathai [12] and Plummer. [13] Plummer et al used a Heidelberg retina tomograph to measure the thickness of the nerve fiber layer in 38 HIV positive patients with or without CMVR and 24 HIV negative controls, and found that the thickness of the nerve fiber layer of HIV positive patients was smaller than that of the controls, regardless of CMVR.…”
Section: Discussionsupporting
confidence: 81%
“…OCT characteristics of patients in the CMVR group: In the present study, the thickness of various macular regions in the CMVR group generally increased, and the reflection of the entorretina increased. [10] This is consistent with the study results reported by Japanese scholar Yashiro et al, [11] but is contradictory to the study results reported by Pathai [12] and Plummer. [13] Plummer et al used a Heidelberg retina tomograph to measure the thickness of the nerve fiber layer in 38 HIV positive patients with or without CMVR and 24 HIV negative controls, and found that the thickness of the nerve fiber layer of HIV positive patients was smaller than that of the controls, regardless of CMVR.…”
Section: Discussionsupporting
confidence: 81%
“…It is distinct in appearance from the early stage CMVR or MVR. In the optical coherence tomography, these white granular lesions showed concavity of the retinal nerve fber layer (RNFL) toward the retinal pigment epithelium and destruction of all retinal layers vertically; while the cotton wool spot showed elevation of the RNFL and no destruction of the retinal structure [7] . We divided it into an independent group and compared it with early stage CMVR group, posterior MVR group and peripheral MVR group in age and CD4+T lymphocyte level.…”
Section: Discussionmentioning
confidence: 97%
“…CMVR was defined through fundus examination showing local or quadrantal retinal necrosis: cheese ketchup necrosis, granular appearance or frosted branch retinal angiitis. CMVR was divided into two categories as follows: (1) initial stage (when the focus is less than one disc diameter and observation was approximately less than one week after onset), (2) early stage (when the initial therapeutic dose of anti-CMV agents is used and the observation was approximately less than 2 to 4 weeks after onset) [7] . For HIV-related MVR, a participant was defined as having posterior or peripheral cotton wool spots, microaneurysms, telangiectasia, or retinal hemorrhages.…”
Section: Introductionmentioning
confidence: 99%
“…The selective EZ disruption may represent early CMV infection via this route and could be recovered if the treatment was initiated promptly before viral induced photoreceptor apoptosis 18 . Some cases with persistent loss of outer layer with preserved inner retinal layers were described 19 . Moreover, evidence of delineate line of hyperautofluorescence along the active leading edge of the retinitis also suggested early involvement at the RPE/photoreceptor level 20,21 .…”
Section: Discussionmentioning
confidence: 99%